A revision of the fern genus Dryopteris (Dryopteridaceae) in sub-Saharan Africa - Roux, Jacobus P. (Phytotaxa, 2012)
The morphology of the Dryopteris species occurring in sub-Saharan Africa is discussed. This is followed by a revision of the genus in this region, and the Cape Verde Islands in the Gulf of Guinea. Twenty-six species are recognised for the region.